Psychological wellbeing and suicidal risk in students of 5th grade of secondary school in the district of Los Olivos - Chávez Chávez, Ana Cristina (2015)
This research entitled Psychological well-being and suicide risk in adolescents in 5th grade school district of Olives, aimed to determine the relationship between these two variables, with a study of basic type and non-experimental, cross-sectional design, having used two questionnaires. It was concluded that: there is a negative relationship between psychological well-being and suicide risk 5th graders secondary district of Olives, which is demonstrated by the Spearman test (Spearman rho = - .236, alpha = .003 significant).